The Earth as a Distant Planet A Rosetta Stone for the Search of Earth-Like Worlds - Vázquez, M.; Pallé, E.; Montañés Rodríguez, P. (Astronomy and Astrophysics Library, 2010)
Is the Earth, in some way, special? Or is our planet but one of the millions of other inhabited planets within our galaxy? This is an exciting time to be asking this old question, because for the first time in history, the answer is within reach. In The Earth as a Distant Planet, the authors set themselves as external observers of our Solar System from an astronomical distance. From that perspective, the authors describe how the Earth, the third planet in distance to the central star, can be catalogued as having its own unique features and as capable of sustaining life. The knowledge gained from this original perspective is then applied to the ongoing search for planets outside the solar system, or exoplanets. Since the discovery in 1992 of the first exoplanet, the number of known planets has increased exponentially. Ambitious space missions are already being designed for the characterization of their atmospheres and to explore the possibility that they host life. The exploration of Earth and the rest of the rocky planets in our Solar System will help us in classifying and understanding the multiplicity of planetary systems that exist in our galaxy. In time, statistics on the formation and evolution of exoplanets will be available and will provide vital information for solving some of the unanswered questions about the formation, as well as the evolution, of our own world. The authors provide an introductory but also very much up-to-date referenced text, making this book useful not only for the layman, but also for researchers and advanced students in Astrophysics and Earth Sciences.